Aksi Kewargaan Membela Hak Ekologi Warga Trenggalek: Analisis Ideologis, Lingkungan, dan Teologis - Yayum Kumai (Badan Strategi Kebijakan Hukum, 2023)
The background of this research aims to publish two reasons. First, to show a new perspective of common opinion about the social movement that is based on the class struggle. In this research, the environmental movement is run by the ecological ideology, spirituality, and theology motives. Second, the protests to reject the mining exploitation agenda are not to fight the state nor hinder the development agenda. However, these are the acts of citizenship as a part of participation in a democratic country. Based on the two points above, the research adapts two concepts those are the acts of citizenship from Engin Isin and humanistic Islam from Anna Gade. The data mining process uses ethnographic or observational participatory method that has done in the field of movement as become part of them. The discussion divides the actors of movement into three categories, two of them are Islamic-based organization and the left one is Javanese spiritual group. Each of them works on their own way to defend the ecological rights, but they all have the similar objectives of movement that is ecological sustainability. To develop the study of human rights movement in Indonesia, the approach of ethnography study needs to be deepened and doubled so that the local perspective about their own construction about rights could be mapped.